2007
DOI: 10.1111/j.1744-6155.2007.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

A Snapshot of Children's Postoperative Tonsillectomy Outcomes at Home

Abstract: Parents need to become partners in pain management. Recommend multimodal discharge teaching and follow-up phone call at home to ensure adequate analgesic administration and fluid intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…With changes to the delivery of health care, increasing numbers of children undergo surgery on an outpatient basis, which leaves the responsibility for management of postoperative pain in the hands of parents. Unfortunately, research has repeatedly documented that parents struggle with optimal pain management of children and, in fact, tend to undermedicate children's acute surgical pain [1,[4][5][6][7][8][9][10][11][12]. The research by our group not only has documented parental undertreatment of children's postoperative pain [1] but also has identified that parental attitudes regarding analgesic use for children are a barrier to optimal pain management.…”
Section: Millions Of Children Undergo Surgery In the Unitedmentioning
confidence: 87%
“…With changes to the delivery of health care, increasing numbers of children undergo surgery on an outpatient basis, which leaves the responsibility for management of postoperative pain in the hands of parents. Unfortunately, research has repeatedly documented that parents struggle with optimal pain management of children and, in fact, tend to undermedicate children's acute surgical pain [1,[4][5][6][7][8][9][10][11][12]. The research by our group not only has documented parental undertreatment of children's postoperative pain [1] but also has identified that parental attitudes regarding analgesic use for children are a barrier to optimal pain management.…”
Section: Millions Of Children Undergo Surgery In the Unitedmentioning
confidence: 87%
“…Despite these findings, parents have been critiqued for undertreating children's pain by withholding prescribed analgesics following surgery (Fortier et al, 2009). Further, many studies suggest that most parents give less than prescribed analgesic doses after surgery in a manner that correlates only poorly to moderately with their children's reported pain intensity (Kankkunen et al, 2003;Rony et al, 2010;Stewart et al, 2012;Vincent et al, 2012;Warnock and Lander, 1998;Zisk et al, 2008;Hamers and Abu-Saad, 2002;Helgadottir and Wilson, 2004;Unsworth et al, 2007;Wiggins and Foster, 2007;Huth and Broome, 2007). Many discontinue analgesics even when pain is ongoing (Warnock and Lander, 1998;Hamers and Abu-Saad, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…Many reasons for the low rates of analgesic administration by parents have been suggested, including fears of medication dependence, lack of understanding of the presentation of pain in young children, and beliefs that analgesics should be used only as a last resort. [3][4][5]25,26 Investigators also found that personality characteristics and sociodemographic factors may affect parents' adherence to pain management recommendations. For example, our group found that parents with less education and more-reactive children gave fewer analgesics, whereas parents rated higher in conscientiousness and those with impulsive children were more likely to provide analgesics to their children postoperatively.…”
Section: Figurementioning
confidence: 99%
“…2 Indeed, researchers outside the United States suggested high levels of pain after tonsillectomy and adenoidectomy, as well as undertreatment of postoperative pain by parents. [3][4][5][6][7][8][9][10][11] The majority of those studies, however, had methodologic limitations such as small sample sizes, limited use of validated pain measures, and lack of a standardized approach to anesthesia and surgery.…”
mentioning
confidence: 99%